0.5-V High-Order Universal Filter for Bio-Signal Processing Applications - Montree Kumngern; Fabian Khateb; Tomasz Kulej; Somkiat Lerkvaranyu (My University, 2025)
In this paper, a novel multiple-input operational transconductance amplifier (MI-OTA) is proposed. The MI-OTA can be obtained by using the multiple-input bulk-driven MOS transistor (MIBD MOST) technique. The circuit structure is simple, can operate with a supply voltage of 0.5 V, and consumes 937 pW at a current setting of 625 pA. The proposed MI-OTA was used to implement a high-order multiple-input voltage-mode universal filter. The proposed filter can provide non-inverting and inverting low-pass, high-pass, band-pass, band-stop, and all-pass transfer functions to the same topology. In addition, it has a high input impedance and does not need any inverted input signals, so there is no additional buffering circuit. The proposed filter can be used for biological signal processing. The proposed MI-OTA and the second-order universal filter were simulated in Cadence using CMOS process parameters of 0.18 μm from TSMC to verify the functionality and performance of the new structures.
Keywords: Photonic and Optical Devices